THE EASE OF DOING BUSINESS IN INDONESIA - Fibra, Adsina (Bina Nusantara University, 2018)
The ease of doing business (EOB) is one of the indicators which attract foreign investors do business in Indonesia. Indonesiaâ€™s ease of doing business has improved from time to time but still left behind compare to other Asian countries. The current research addresses research questions; what are the business reforms which have been done by Indonesian Government in a last decade to promote the ease of doing business, what are the areas need to be improved, and how the ease of doing business gives advantages to this developing nation. Â This study contributes to reveal the implementation of EOB policy in Indonesia; enrich EOB policy literature; and suggest recommendations for EOB improvement.